Antiapoptotic Effect of Simvastatin Ameliorates Myocardial Ischemia/Reperfusion Injury. (19th December 2013) - Hadi, Najah R.; Al-amran, Fadhil; Yousif, Maitham; Zamil, Suhaad T.
Abstract : Background . Myocardial ischemial reperfusion represents a clinically relevant problem associated with thrombolysis, angioplasty, and coronary bypass surgery. Injury of myocardium due to ischemial reperfusion includes cardiac contractile dysfunction, arrhythmias, and irreversible myocytes damage. These changes are considered to be the consequence of imbalance between the formation of oxidants and the availability of endogenous antioxidants in the heart. Objective . This study was undertaken to investigate the potential role of Simvastatin in the amelioration of myocardial I/R injury induced by ligation of coronary artery in a rat model. Materials and Methods . Adult male Swiss Albino rats were randomized into 4 equal groups. Group (1): sham group: rats underwent the same anesthetic and surgical procedures as those in the control group except ligation of LAD coronary artery, group (2): control group: rats were subjected to regional ischemia for 25 min and reperfusion for 2 hours by ligation of LAD coronary artery, group (3): control vehicle group: rats received vehicle of Simvastatin (normal saline) via IP injection and were subjected to regional ischemia for 25 min and reperfusion for 2 hours by ligation of LAD coronary artery, group (4): Simvastatin treated group: rats were pretreated with Simvastatin 1 mg/kg i.p. 1 hr before ligation of LAD coronary artery. At the end of experiment (2 hr of reperfusion), blood samples were collected from the heart for the measurement of plasma level of cardiac troponin I (cTnI). After that the heart was harvested and divided into 3 parts; one part was used for measurement of apoptosis, another part was homogenized for the measurement of tissue tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), interleukin-6, monocyte chemoattractant protein-1, and macrophage inflammatory protein-1 α, and the last part for histopathology study. Results . Compared with the sham group, levels of myocardial TNF- α and IL-1 β, IL-6, MCP-1, and MIP-1 α and plasma cTnI were increased (P < 0.05 ). Histologically, all rats in control group showed significant (P < 0.05 ) cardiac injury. Furthermore, all rats in control group showed significant (P < 0.05 ) apoptosis. Simvastatin significantly counteracted the increase in myocardium level of TNF- α, IL-1B, IL-6, MCP-1 and MIP-1 α, plasma cTnI, and apoptosis (P <   0.05 ). Histological analysis revealed that Simvastatin markedly reduced (P <   0.05 ) the severity of heart injury in the rats that underwent LAD ligation procedure. Conclusions . The results of the present study reveal that Simvastatin may ameliorate myocardial I/R injury in rats via interfering with inflammatory reactions and apoptosis which were induced by I/R injury.